Analisis Interaksi Obat-Obat Kardiovaskular pada Pasien Jantung Koroner dengan Riwayat Hipertensi - Febriyenti, Amanda; Yosmar, Rahmi; Permatasari, Dita (Journal of Pharmaceutical and Sciences, 2025)
Coronary heart disease (CHD) accompanied by hypertension often necessitates the use of multiple cardiovascular agents. The concurrent use of multiple drugs increases the risk of drug-drug interactions (DDIs), which may alter drug metabolism, reduce therapeutic efficacy, or cause adverse effects. This study aimed to characterize the potential, mechanisms, and severity of drug interactions; to assess differences in the average number of drugs used per day in relation to the potential for drug interactions; and to assess the clinical profile based on DDI severity levels. A retrospective, analytic, observational method was applied, utilizing secondary data from hospital medical records. Statistical analysis included the Mann–Whitney test to compare the mean number of drugs per day between the interaction potential groups. A total of 52 patients met the inclusion criteria through purposive sampling. The results showed that most CHD patients with a history of hypertension were male (75%) and aged 18–64 years (73.1%). A total of 405 potential DDIs were identified. From these, 80 unique drug-pair interactions were selected for detailed analysis of their mechanisms and severity. Most were pharmacodynamic (77.5%), with aspirin–nitroglycerin the most frequent (7.6%). Among the 80 interactions analyzed in detail, those with moderate severity predominated (58.8%), followed by minor (35%) and major (6.2%). Polypharmacy (defined as the use of three or more medications) was observed in all patients who experienced DDIs. There was a significant difference in the average number of medications per day between patients with potential drug interactions and those without, p = 0.023 (p < 0.05).